People, Process, Technology, and Partner in Hospital Supply Chain Management: A Systematic Literature Review - Setiawati, Marla; Simatupang, Togar Mangihut; Okdinawati, Liane (Politeknik Negeri Bandung, 2024)
This systematic review aims to identify gaps in the areas of people, processes, technology, and partners within hospital supply chain management. The analysis followed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to ensure a rigorous and comprehensive approach. The review identified significant gaps in each area. In terms of people, two key gaps were observed. First, there is a lack of research exploring the impact of hospital supply chain management on patients, particularly in relation to patient satisfaction and healthcare outcomes. Second, there is limited attention given to the role of government policies and regulations in shaping and influencing hospital supply chain management practices. Regarding the process, the review identified a gap in the understanding of service delivery within hospital supply chain management. In the area of technology, gaps were found in research related to specific technological applications. Specifically, there is a limited focus on the utilization of radio frequency identification (RFID), information technology (IT), and blockchain in hospital supply chain management. Exploring the potential benefits and challenges associated with these technologies would contribute to more efficient inventory management, enhanced traceability, and improved data security. Lastly, the review identified a gap in understanding the dynamics and effectiveness of partnerships within hospital supply chain management. Limited research has explored the strategies and best practices for establishing and managing partnerships with suppliers, distributors, and manufacturers. Investigating successful partnership models and factors influencing their effectiveness would enable hospitals to optimize collaboration efforts and achieve improved supply chain performance.